Analytical Hierarchy Process (AHP) Approach for CCTV Vendor Selection in Goods Procurement - Siwalette, Michael; Muslim, Aries (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
Selecting CCTV devices and vendors is a complex process because it involves many criteria, such as reputation/rating, price, distance, delivery time, and warranty period. Financing companies face difficulties in conducting these evaluations because the process is still manual, there are no standard criteria, and it requires many stages of approval that hinder the process. This study designs a web-based decision support system using the Analytic Hierarchy Process (AHP) method to assist in the objective selection of CCTV equipment. This system considers three main criteria: price, delivery time, and warranty period. The calculation results show that the system produces consistent recommendations, with a consistency ratio (CR) value below 0.1. The system also addresses zero data in alternatives by replacing zero values with small (non-zero) numbers to maintain the validity of AHP calculations. Repeated testing shows stable results even with different data. Thus, this system provides an efficient, transparent, and standardized solution in the CCTV device procurement process at financing companies